Group pain neuroscience education and dance in institutionalized older adults with chronic pain: a case series study. (2nd January 2022) - Simões, Patrícia; Andias, Rosa; Simões, Diana; Silva, Anabela G.
ABSTRACT: Introduction : The use of pain neuroscience education in older adults has seldom been reported. While this age group shows high rates of chronic pain prevalence, its characteristics may also challenge an intervention of this nature. This case series aimed to describe a group intervention of pain neuroscience education and dance in institutionalized older adults with chronic pain. Case Series : Seven older adults institutionalized in a day care center/nursing home with chronic pain entered the study and received a group intervention of six sessions of pain neuroscience education and dance. Participants were assessed at baseline and at the end of the intervention regarding knowledge of pain neurophysiology, pain intensity, depressive symptoms, catastrophizing, fear of movement and lower limb performance. Outcomes : There was a mean (±SD) decrease of −1.0 ± 2.3 for pain intensity and of −6.1 ± 9.7 for pain catastrophizing and a mean increase in the score of the pain neurophysiology questionnaire of 4.0 ± 3.1. Mean change values were smaller than the minimal detectable difference, but a few individual participants changed above the minimal detectable difference (four participants for pain intensity and 2 for pain catastrophizing and knowledge of pain neurophysiology). Conclusion : Results suggest pain neuroscience education is a feasible intervention and when combined with dance may have a positive impact on pain intensity.